2001
DOI: 10.1073/pnas.211303598
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of euchromatic genes by Drosophila heterochromatin protein 1 and histone modifiers

Abstract: In Drosophila, heterochromatin protein 1 (HP1) suppresses the expression of euchromatic genes that are artificially translocated adjacent to heterochromatin by expanding heterochromatin structure into neighboring euchromatin. The purpose of this study was to determine whether HP1 functions as a transcriptional repressor in the absence of chromosome rearrangements. Here, we show that Drosophila HP1 normally represses the expression of four euchromatic genes in a dosage-dependent manner. Three genes regulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 31 publications
2
81
0
Order By: Relevance
“…Interestingly, one of the genes misregulated in the HP1 homozygous mutant maps to cytological region 31, a chromosome division that stains intensely with antibodies to HP1 (7). Two additional randomly selected genes within region 31 show up-regulation in HP1 homozygous mutants (59). For all four candidate HP1 target genes, mutations in additional modifiers of PEV, including Su(var)3-9, cause increases in gene expression.…”
Section: Hp1 Regulates Gene Expressionmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, one of the genes misregulated in the HP1 homozygous mutant maps to cytological region 31, a chromosome division that stains intensely with antibodies to HP1 (7). Two additional randomly selected genes within region 31 show up-regulation in HP1 homozygous mutants (59). For all four candidate HP1 target genes, mutations in additional modifiers of PEV, including Su(var)3-9, cause increases in gene expression.…”
Section: Hp1 Regulates Gene Expressionmentioning
confidence: 98%
“…HP1 associates with origin recognition complex (ORC) proteins (58,59). This presents an intriguing parallel to the situation in Saccharomyces cerevisiae where ORC proteins associate with silent information regulator (SIR) proteins to generate silent chromatin (60,61).…”
Section: Hp1 Interacts With a Myriad Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 and 39); however, the precise mechanisms of HP1 repression are not well understood. HP1 has been shown to play a role not only in heterochromatic silencing but also in normal repression of genes in euchromatin (51). In mammalian cells and Schizosaccharomyces pombe, it has been reported that HP1͞Swi6 chromodomain binds to histone H3 methylated by the methyltransferase SUV39H1͞Clr4 at Lys-9 (52-54).…”
Section: Gal4-hp1 Fusions Repress Transcriptional Activation By Htafimentioning
confidence: 99%
“…SU(VAR)3-9 (Hwang et al 2001) ] strongly suppress PDS. Therefore these zinc fingers are necessary for SU(VAR) 3-7-dependent silencing in vivo.…”
mentioning
confidence: 99%